The skilled diaspora: an analysis of the situation of Mexicans with higher education in the United States - Álvarez Blanco, Imanol; Bautista León, Andrea (Revista Internacional de Salarios Dignos, 2024)
This research analyzes the skilled migration of Mexicans to the United States. In particular, it studies the mismatch between educational training and job opportunities in both Mexico and the United States with the construction of three contrasting groups: 1) Mexicans in Mexico with higher education, 2) Mexicans in the United States with higher education, and 3) Americans (white/non-Hispanic) with higher education. A recent period (2022-2023) is studied where 33% of migrants in OECD countries, including the 1,313,666 Mexicans in the US, have post-secondary education, of which only 42.8% obtain professional jobs in line with their training. The Mexican National Occupation and Employment Survey (ENOE) and the US Integrated Public Use Microdata Series (IPUMS) were used as sources of information. The study categorizes individuals by nationality and education, focusing on gender differences and the wage “premium” of education. Among the results, it was found that Mexicans with higher education in Mexico have a higher wage “premium” in relative terms compared to those who migrate and that Mexican women abroad have a smaller gap relative to US women. At the same time, male migrants have a more significant wage gap than their US peers.